Analisis Potensi Pasar Aurduri Dan Perannya Dalam Meningkatkan Kesejahteraan Pedagang - Risa Evrilia; Putri Apria Ningsih; Kurniyati Kurniyati (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Traditional markets involve many small and medium enterprises which are relatively large in number compared to the existence of modern markets whose expertise tends to be controlled by only a few people who have large capital. The purpose of this study is to determine the market potential for traders and the role of the auduri market in improving trader welfare. The type of research method used is qualitative research, using the type of field research (field research. The results of this study reveal that the potential of the auduri market towards traders is very good. This is evidenced by the results of research on 35 traders who said the auduri market has a location close to community settlements, high purchasing power of the community for the goods offered and the existence of a market structure. While the role of the market in improving the welfare of traders can be seen from the results of research that reveals traders feel helped by them selling there. From the proceeds they can meet the needs of their families, send their children to school and those who were once unemployed to have jobs. So it can be concluded that the role of the auduri market is very helpful for them in the economic welfare of their families.